FUNDAMENTAL AND APPLICATIONS OF OPERATIONAL AMPLIFIER - HASSAN, HASLIZA (2024)
“Fundamental and Applications of Operational Amplifiers” explores the complex world of operational amplifiers or op-amps and looks at the theoretical foundations as well as real-world uses for these crucial electrical components. Written as an all-inclusive reference for electronics novices and experts alike, this book provides  a complete overview of op-amps, encompassing their basic principles, sophisticated ideas, and wide range of applications in many fields.The book  begins by providing a solid foundation in  the basic principles of operational amplifiers, elucidating topics such as ideal op-amps characteristics, input-output configurations and basic circuit analysis techniques. Through clear explanations and illustrative examples, readers gain a deep understanding of op-amp behaviour and operation.Building upon this foundation, the book progresses to explore more advanced topics, including frequency response, stability analysis and noise considerations. By delving into these intricacies, readers are equipped with the knowledge to design and analyzed op-amp circuit with precision and efficiency. Moreover, “Fundamental and Applications of Operational Amplifiers” goes beyond theoretical discussions to present a plethora of real-world applications. From signal conditioning and instrumentation amplifiers to active filters and oscillators, the book showcases how op-amps are utilized in diverse electronic circuits across industries.Whether you are a student, hobbyist, or seasoned engineer, “Fundamental and Applications of Operational Amplifiers” serves as an invaluable resource for mastering the principles and applications of these ubiquitous electronic components. With its comprehensive coverage, practical insights and illustrative examples, this book empowers readers to harness the full potential of operational amplifiers in their electronic designs and projects.